An Analysis Of Morphological Error In English Word Formation Process Made By The Third Semesrter Students Of English Education Department Madura Islamic University - Samsi Rijal (PROCEEDING UMSURABAYA, 2019)
This research begins from the observation at teaching and learning process of English language as foreign language especially at the English Morphology class, the researcher found some studentsâ€™ problems related to the analyzing of English word formation process through tree diagram. They felt difficulties in analyzing English word formation process particularly in combining prefixes and suffixes.Â  In this research, the researcher used descriptive qualitative which is the objective to describe the morphological error in analyzing the English word formation. The subject of this research is the third semester students of academic year 2018/2019 at English Education Department FKIP Madura Islamic University. In collecting the data, the researcher used the test and document study. The result of the research, the students understand well the function of every affixes in English word formation process but they made some errors in analyzing English word formation in multi word formation processes especially in combining prefix and suffix, derivational affix and inflectional affix.Keywords: Word Formation, prefixes, suffixes.